Testing and Analysis of Energy-Efficient Solar Lamp Performance on Sulawesi Island - Hulukati , Stephan Adriansyah; Sholihah, Qomariyatus; Harahab, Nuddin; Marjono, Marjono (Indonesian Green Technology Journal, 2024)
The Energy-Efficient Solar Lamp (LTSHE) initiative is a strategic electrification program implemented by the Indonesian government to deliver sustainable lighting solutions to rural communities in Sulawesi that remain beyond the reach of the national electricity grid. The program primarily targets residents in remote, underdeveloped, and isolated areas, including border regions and small frontier islands. The LTSHE system utilizes photovoltaic panels to capture solar energy, which is converted into electrical energy and stored in lead-acid batteries through a capacitor hub, subsequently supplying power to LED lamps for household illumination. To assess system performance, a photometric evaluation was conducted on a sample representing 6,018 installed systems (24,072 lamp units). As of July 31, 2018, nine units (0.037%) were randomly selected for laboratory testing. Illumination intensity was measured at three dimming levels (100%, 50%, and 10%), producing average illumination values of 31.6 lux, 15.4 lux, and 3.2 lux, respectively. Measurements at reduced dimming levels demonstrated consistent light output across samples, with values ranging from 14.4 to 14.8 lux at 50% and approximately 2.8 lux at 10%. Laboratory verification also indicated that the measured direct current injection voltage (8.10 V) exceeded the manufacturer’s specified minimum of 7.40 V, confirming the accuracy and reliability of the testing instruments. Overall, the findings demonstrate that LTSHE units provide adequate and consistent illumination, particularly at lower dimming settings, supporting their suitability for off-grid rural applications in Sulawesi. Future evaluations are recommended to standardize testing across all dimming levels to ensure comprehensive performance validation.